Beiträge zur Insektenfauna der DDR: Lepidoptera - Nymphulinae, Schoenobiinae, Acentropidae. - Rinnhofer, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1988)
On the basis of the evaluation of literature and collections and of planned collecting, 8 species of Microlepidoptera of the subfamilies Nymphulinae and Schoenobiinae and of the family Acentropidae could be established for the territory of the GDR. By reason of their similar modes of life, greatly depending on water, these species are grouped together. With the exception of Schoenobius gigantellus (D. & S.) and Donacaula mucronella (D. & S.) they seem to be rather evenly distributed and frequent in the territory under discussion, though collecting especially in the districts of Suhl and Leipzig was done somewhat at random. The faunistic part of the paper is supplemented by sections on the flying period of the butterflies, the feed plants of the caterpillars, a key according to wing patterns and black-and-white photographs of the wings of all species.